Beyond GDP and Back: What Is the Value-Added by Additional Components of Welfare Measurement? - Sonja C. Kassenböhmer; Christoph M. Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Recently, building on the highly polarizing Stiglitz report, a growing literature suggests that statistical offices and applied researchers explore other aspects of human welfare apart from material well-being, such as job security, crime, health, environmental factors and subjective perceptions. To explore the additional information of these indicators, we analyze data on the macro level from the German Federal Statistical Office combined with micro level data from the German SOEP (1991-2008) on the personal work situation and subjective feelings concerning several aspects of life. Employing the indicators suggested by the Stiglitz Report, we find that much of the variation in many well-being measures can indeed be captured well by the hard economic indicators as used in the literature, especially by GDP and the unemployment rate. This suggests that the hard indicators are still a reasonable and quite robust gauge of well-being of a country. And yet, we also see that these correlations are far from perfect, thus giving considerable hope that there is room for a broader statistical reporting.
Keywords: D6; I3; E1; C38; 330; Stiglitz Commission; Stiglitz Report; Beyond GDP; welfare measurement; life satisfaction; Bruttoinlandsprodukt; Kritik; Sozialer Indikator; Messung; Zufriedenheit; Arbeitszufriedenheit; Schätzung; Deutschland